Analysis of the Role of Supeltas as Informal Traffic Controllers at the Jambon Intersection - Isnawan, Fuadi (Journal of Law, Politic and Humanities, 2025)
Traffic congestion is a classic problem in urban areas, including in the Sleman region of the Special Region of Yogyakarta. One of the most significant congestion hotspots is the Jambon Four-Way Intersection, where traffic flows from various directions converge. In addressing this congestion, the strategic role of Traffic Volunteers (Supeltas) emerges, who voluntarily assist in regulating traffic flow. Their presence often serves as a temporary solution to alleviate congestion, especially during peak hours. This study aims to identify and analyze the role of Supeltas at the Jambon Four-Way Intersection and evaluate the need for a management and training system for them in the future to ensure greater effectiveness and sustainability. The study employs an empirical method using direct observation as the data collection technique. The results of the study indicate that Supeltas make a concrete contribution to reducing traffic congestion and fostering good two-way communication with drivers, thereby helping to create a sense of safety and order on the roads. However, they still operate without clear system support and are not integrated into formal traffic management. Therefore, future efforts are needed in the form of training, capacity building, and institutional strengthening involving the police, local government, and the community. This is important to maintain the consistency of Supeltas' role, enhance professionalism, and provide legal protection for them. With a more structured and collaborative approach, Supeltas can become strategic partners in creating safer, more orderly, and more humane traffic in urban areas.